Alveolar gas exchange and tissue oxygenation during incremental treadmill exercise, and their associations with blood O2 carrying capacity - Rissanen, Antti-Pekka E.; Tikkanen, Heikki O.; Koponen, Anne S.; Aho, Jyrki M.; Hägglund, Harriet; Lindholm, Harri; Peltonen, Juha E. (Frontiers in Physiology, 2012)
The magnitude and timing of oxygenation responses in highly active leg muscle, less active arm muscle, and cerebral tissue, have not been studied with simultaneous alveolar gas exchange measurement during incremental treadmill exercise. Nor is it known, if blood O2 carrying capacity affects the tissue-specific oxygenation responses. Thus, we investigated alveolar gas exchange and tissue (m. vastus lateralis, m. biceps brachii, cerebral cortex) oxygenation during incremental treadmill exercise until volitional fatigue, and their associations with blood O2 carrying capacity in 22 healthy men. Alveolar gas exchange was measured, and near-infrared spectroscopy (NIRS) was used to monitor relative concentration changes in oxy- (Δ[O2Hb]), deoxy- (Δ[HHb]) and total hemoglobin (Δ[tHb]), and tissue saturation index (TSI). NIRS inflection points (NIP), reflecting changes in tissue-specific oxygenation, were determined and their coincidence with ventilatory thresholds (anaerobic threshold (AT), respiratory compensation point (RC); V-slope method) was examined. Blood O2 carrying capacity (total hemoglobin mass (tHb-mass)) was determined with the CO-rebreathing method. In all tissues, NIPs coincided with AT, whereas RC was followed by NIPs. High tHb-mass associated with leg muscle deoxygenation at peak exercise (e.g., Δ[HHb] from baseline walking to peak exercise vs. tHb-mass: r = 0.64, p < 0.01), but not with arm muscle- or cerebral deoxygenation. In conclusion, regional tissue oxygenation was characterized by inflection points, and tissue oxygenation in relation to alveolar gas exchange during incremental treadmill exercise resembled previous findings made during incremental cycling. It was also found out, that O2 delivery to less active m. biceps brachii may be limited by an accelerated increase in ventilation at high running intensities. In addition, high capacity for blood O2 carrying was associated with a high level of m. vastus lateralis deoxygenation at peak exercise.